Tissue Culture Propagation of “Hausa potato” (Solenostemon rotundifolius (Poir) JK Morton) - Witjaksono, Witjaksono; Leksonowati, Aryani (BRIN, 2012)
We have developed an effective plant propagation method of „hausa potato‟ through shoot proliferation in vitro, acclimatization in the greenhouse and transplantation of the plantlet on the individual media container for planting material production. The shoot cultures were initiated from shoots that grew from tuber collected from the field, disinfested using standard method and transferred to MS medium with 1 mg/l of BA for shoot proliferation. The proliferating shoots were then subcultured to MS medium with no growth regulators to induce rooting and enlarge the shoot. The plantlets were acclimatized in a plastic box containing medium of a mixture of cocopeat, sands, rice husk charcoal and top soil covered with plastic film to maintain humidity. The plantlets survived at 85% and almost 100% grew into planting materials ready for transplanting in the soil. The planting materials survived in the field and produced tuber normally.